59.1k views
2 votes
Please help me solve this​

Please help me solve this​-example-1
User Pierry
by
5.4k points

1 Answer

3 votes

You can factor the 32 out of the sum:


\displaystyle \sum_(m=1)^\infty 32 \cdot \left((1)/(2)\right)^(m-1) = 32\sum_(m=1)^\infty \left((1)/(2)\right)^(m-1)

We can also change the index as follows


\displaystyle 32\sum_(m=1)^\infty \left((1)/(2)\right)^(m-1) = 32\sum_(m=0)^\infty \left((1)/(2)\right)^(m)

Now, we have a theorem that states that the series


\displaystyle \sum_(m=1)^\infty a^m

converges if and only if
|a|<1, and in this case we have


\displaystyle \sum_(m=1)^\infty a^m = (1)/(1-a)

This is your case, because you have


|a|=(1)/(2)<1

which implies that your series converges, and the value is


\displaystyle 32\sum_(m=0)^\infty \left((1)/(2)\right)^(m) = 32 \cdot (1)/(1-(1)/(2)) = 32\cdot 2 = 64

User Dmazzoni
by
5.3k points